Determinan Audit Delay pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sampriyani Sihombing; Dian Puji Puspita Sari; Mentari Dwi Aristi (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This research aims to partially examine the influence of company size, solvency, profitability, KAP reputation and auditor opinion on manufacturing companies. The population of this study are all manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange during the 2017-2021 period. The sampling method in this research uses a purposive sampling method, namely by drawing samples based on certain considerations that are tailored to the interests and objectives of the research. The data analysis technique used is multiple linear regression analysis with a significance level of 0.05. The type of data used in this research is secondary data in the form of financial reports and independent audit reports for 2017 - 2021. The results of this research show that company size and solvency have no effect on audit delay. As well as profitability, KAP reputation and auditor opinion have an effect on audit delay